PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DAPAT MENINGKATKAN PRESTASI BELAJAR DAN AKTIVITAS MATA PELAJARAN IPS SISWA KELAS V SD NEGERI 6 KENDARI - Wa Hudia (CV. ADIBA AISHA AMIRA, 2023)
This research was carried out to develop methods or steps for social studies learning in class V SD Negeri 6 Kendari by applying the STAD type cooperative learning model. This research is a classroom action research in the form of collaboration with other teachers which was carried out for two cycles in the odd semester of 2019. The main objective of this research is to formulate cooperative learning steps for social studies with the STAD type. In addition, it also aims to determine the impact of implementing these main objectives, namely 1) teacher activities in implementing cooperative learning, 2) student activities in cooperative groups, 3) student perceptions of the application of cooperative learning models, and 4) student achievement in mathematics taught by cooperative learning. This research provides benefits in increasing the ability to research teachers in schools, especially for teachers in developing classroom learning through action research. The results of this study indicate that student learning activities in the first cycle of learning interaction are still lacking, this has implications for their learning achievement, but in the implementation of the second cycle, the frequency of students helping each other and asking other students so that it has implications for their learning achievement. The results of this study showed that students' mathematics learning achievement increased significantly with an average score of 76.83 in cycle II and this was better than the average score of 60.75 in cycle I. In cycle II there were also 34 students (85%) who have achieved learning mastery. As the implications obtained from the results of this study, it is suggested that social studies learning is student-centered and carried out with STAD type cooperative learning.